Systematic investigation on fluid flow and heat transfer characteristic of a tube equipped with variable pitch twisted tape. (February 2020) - Paneliya, Sagar; Khanna, Sakshum; Patel, Umang; Prajapati, Parth; Mukhopadhyay, Indrajit
Abstract: In this paper, we report an experimental and Computational Fluid Dynamics (CFD) modeling to investigate heat transfer rate ( Q ), overall heat transfer coefficient ( U ), friction factor ( f ), thermal enhancement factor ( η ) and effectiveness ( ℇ ) of a tube equipped with constant and variable pitch twisted tape inserts. The pitch by width ratio ( Y ) for constant and variable pitch twisted tape insert used in the experiment was 4 and 4-3-4 respectively. The material of inserts used during the investigation were aluminum and stainless steel due to their ease in machinability. An enhancement in heat transfer rate was observed due to the presence of twisted tape inserts imposing turbulence and swirling flow motion in the test tube. Further, it was observed that the heat transfer coefficient, effectiveness and thermal enhancement factor of variable pitch twisted tape were significantly higher than constant pitch tape inserts. Experimental data obtained were validated using Computational Fluid Dynamics (CFD) simulations. The constant pitch inserts showed an enhanced heat transfer rate of 2.08 times as compared to plain tube. The aluminum and stainless-steel variable pitch twisted tape inserts showed an enhancement of overall heat transfer coefficient of 23.81% and 22.36%, respectively, compared to constant pitch tape insert.